Insole Gait Acquisition System Based on Wearable Sensors - Gogoi, Niharika; Fischer, Georg; Kirchner, Jens; Yu, Zixuan; Qin, Yichun (Engineering Proceedings, 2021)
Human gait analysis is a growing field of research interest in medical treatment, diagnosis, sports training, and structural health monitoring. It is the study of graphical representation of human motion through observation method (video or image-based) in a clinical setup or placing sensor method at different parts of the body, to understand the condition of human muscles, mechanics, and fitness. Out of the two methods, the role of wearable sensors in such clinical applications is crucial because of their low cost, simple implementation, and time to time monitoring. In our study, we propose an insole design for wearable sensors based on lead zirconate titanate piezoelectric discs (PZT) and inertial measurement unit (IMU) BMI270 to acquire the human gait. A PZT and an IMU aligned on the same axis are placed in a metallic structure. Such structures are placed at three points of a shoe sole: toe, metatarsal, and heel. The human gait obtained from this insole layout is significantly affected by plantar pressure distribution and alignment of the feet. The PZT sensors give an insight into the pressure map under the feet in the form of voltage. The accelerometer in the IMU gives the change of position of the feet to examine the gait analysis. The gyroscope in IMU is used for the understanding of the motion and posture of feet by measuring its angular rate. The acquired data from these sensors shows that each individual has a different gait pattern at the three points in the sole. It also shows intra-individual variations where the gait of the same person varies in daily situations.<br